Analysis Effect of Exhaust’s Temperature, Total of Peltier’s Element and Circuit Type for Thermoelectric Generator Output Voltage at Exhaust Internal Combustion Vehicle - Setyowidodo, Irwan; Fadhila, Achmad Tri; Mufarri, Am. (Institut Teknologi Sepuluh Nopember, 2018)
This research based on researcher observation about internal combustion vehicle energy percentage, there is 40% energy flow away as high temperature exhaust gas. That percentage could converted as electricity energy with thermoelectric generator concept using peltier element. Purpose of this research are (1) getting optimum exhaust’s temperature to produce highest voltage, (2) getting optimum total of peltier elemen to produce highest voltage, (3) getting optimum circuit type to produce highest voltage, (4) getting optimum Seebeck coefficient point. This research is using L20 orthogonal matrix with three replication and design experiment factorial method. Independent variable that varied are exhaust’s temperature, total of peltier element and circuit type. Response variable in this research is output voltage that analyzed with Anova and contrast test (Scheffe’s method). This research’s result and conclusion is all combination that run simultaneous giving an effect at thermoelectric generator’s voltage, in Anova result. Based on main effect plot and contrast test, optimum combination factor for highest voltage are 2400C exhaust’s temperature, four peltier element in series circuit. Highest Seebeck coefficient at 0,0524 V/K. From this research, researcher suggest thermoelectric generator implimentation at exhaust internal combustion vehicle to use factor combination 2400C exhaust’s temperature, four peltier element in series circuit